2004
DOI: 10.1021/ac0492923
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Assisted Solvent Extraction of Triazines, Organochlorine, and Organophosphorus Compounds in Complex Samples Combined with Large-Volume Injection-Gas Chromatography/Mass Spectrometric Detection

Abstract: The performance of the fully automated membrane-assisted solvent extraction was investigated for 47 environmental contaminants (among them 30 organochlorine compounds, 9 organophosphorus compounds, and 7 triazines). The extraction took place in a 20-mL headspace vial filled with the aqueous sample and containing a polypropylene membrane bag with 1 mL of cyclohexane as extractant. This device was handled by a multipurpose sampler, which enabled the sample to be mixed at a defined temperature with subsequent lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…The membrane is commonly inexpensive and could work as a filter to prevent extraction of larger molecules and interferences for sample clean-up procedures (Lambropoulou et al 2007) e.g. flat membrane from low-density polyethylene glycol (Hauser et al 2001), dense polypropylene bags (Hauser et al 2004). Nonpolar solvents (heptane, cyclohexane) were preferred as acceptor phase.…”
Section: Sample Preparation Procedures For Organochlorinated Pollutantsmentioning
confidence: 99%
“…The membrane is commonly inexpensive and could work as a filter to prevent extraction of larger molecules and interferences for sample clean-up procedures (Lambropoulou et al 2007) e.g. flat membrane from low-density polyethylene glycol (Hauser et al 2001), dense polypropylene bags (Hauser et al 2004). Nonpolar solvents (heptane, cyclohexane) were preferred as acceptor phase.…”
Section: Sample Preparation Procedures For Organochlorinated Pollutantsmentioning
confidence: 99%
“…cyclohexane and ethyl acetate for sage and thyme, and ethyl acetate for coffee. The variation over time (1,5,10,20 and 40 min) of solvent contribution (DRA%) to recovery versus an empty PDMS tubing was determined. Figure 5 shows how the extraction time camphor.…”
Section: Solvent-modified Pdms Versus Recovery Over Time and Inner Somentioning
confidence: 99%
“…Lehotay and coworkers [12][13][14] introduced solvent in silicone tube extraction as an approach to be combined with the QuEChERS (quick, easy, cheap, effective, rugged and safe) method to reduce the detection limit of 26 pesticides analysed at the ppb level, using acetonitrile as inner solvent in PDMS tubing, in combination with GC-MS. Sandra and coworkers [15][16][17] introduced silicon membrane sorptive extraction (SMSE), and used ethyl acetate as solvent to concentrate and then quantify atrazine and its three metabolites in water samples in the 1-10 ppt range by GC-SIM-MS and LC-MS. Van Hoeck also investigated the influence of ethyl acetate as inner PDMS solvent on recovery of EDCs (endocrine disrupters) and pharmaceuticals of different polarity (K O/W between 0 and 4) from a salted-out standard solution at the ppt level and found that SMSE was more effective than SBSE only for very polar compounds (K O/W o2) [18]. Hauser et al [19,20] and Schellin et al [21][22][23] applied the same approach (membrane-assisted solvent extraction) in a fully automatic analysis system using a tubing of dense polypropylene as ''sorptive'' membrane medium, filled with 500-800 mL of hexane or cyclohexane as acceptor solvent, and triazines, 2,4-dichloroanilines, a-HCH and phenanthrene as model compounds; the resulting solution was then online analysed by large-volume injection GC-MS [19]. They also applied this technique to determine polychlorinated biphenyls [20], organophosphorus pesticides as such [21] or together with triazines and organochlorine compounds [22] in several real-world water samples and other matrices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, quite a number of solventless and solvent-minimized sample preparation techniques have been developed, validated and applied in the analysis of trace level pesticide contaminants from various water systems and other matrices [7] [8] [9]. However, most of these techniques have their own limitations; for example, passive dosimetry [10] requires longer sample exposure times while membrane assisted solvent extraction (MASE) [11] uses longer extraction times to ensure quantitative analyte enrichment, typically 1 h; a non-selective characteristics of the extraction solvents in dispersive liquidliquid microextraction (DLLME) [12]; limited applications of stir bar sorptive extraction (SBSE), not suiting for strongly polar compounds unless derivatized [13]. On the other hand, the apparatus needed for most of these techniques are expensive and may not easily be available in most laboratories of the developing countries.…”
Section: Introductionmentioning
confidence: 99%